Performance of the below ground root biomass in different grasslands of Mayabeque province, Cuba - Rodr?guez, Idalmis; Hern?ndez, L.; Crespo, Gustavo; Sandrino, Bertha; Fraga, S. (Cuban Journal of Agricultural Science, 2013)
For studying the below ground root biomass performance in different grasslands of Mayabeque province, six dairy? production units located in San Jos? de las Lajas municipality were selected. They had different types of soils, grasslands and management systems. Samplings were carried out in both climatic periods and in each unit the most representative areas were chosen. Through a transept three soil samples were collected with 50 mm diameter cylinders, at two depths (0-5 and 5-10) to determine the below ground root biomass. In the studied profiles more than 80 % of the below ground root biomass is found in the soil layer 0-5 cm. There was no interaction between season and soil layer in the different daily units. Results obtained are great interest, since they evidence the potential contribution of organic matter to the soil. Also, from them the indices and diagnoses of soil resource can be predicted. Key words: below ground root biomass, grasslands, grasses